Job satisfaction of reference librarians and catalogers in university libraries in the Philippines - Botictic, Corazon L.; Soledad, Daisy R.; Hidalgo, Namnama P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1987)
The purpose of this study is to determine whether there is a significant difference in job satisfaction between two distinctive functional groups in university libraries: catalogers and reference librarians. The subjects of the study consisted of 66 reference librarians and 58 catalogers representing 47 libraries in the Philippines.
The long form version of the Minnesota Satisfaction Questionnaire (MSQ) served as the main instrument in collecting data through direct mailing. "Job Satisfaction" was treated as "General Satisfaction", an aggregate of satisfaction scores of twenty occupational dimensions separately measured by the MSQ: Ability Utilization, Achievement, Activity, Advancement, Authority, Library Policies and Practices, Compensation, Co-workers, Creativity, Independence, Moral Values, Recognition, Responsibility, Security, Social Service, Social Status, Supervision--Human Relations, Supervision--Technical, Variety, and Working Conditions.
The t-test performed on the mean scores of General Satisfaction of catalogers and reference librarians showed no significant difference in the level of General Satisfaction between the two groups at the .05 level of confidence. One-way analysis of variance revealed that satisfaction of the two groups differed significantly with respect to three dimensions: Library Policies and Practices (p<.01), Recognition (p<.05), and Social Status (p<.05). In all three cases, catalogers scored lower than reference librarians.
It is concluded that catalogers and reference librarians do not differ significantly in the level of general satisfaction. However, catalogers are significantly less satisfied than reference librarians regarding a) Library Policies and Practices -- the way library policies are put into practice, b) Recognition -- the praise one gets for doing a good job; and c) Social Status -- the chance to be "somebody" in the community.
Typescript.
Thesis (Master of Library Science)--University of the Philippines Diliman
Keywords: Job satisfaction--Catalogers--Philippines.; Job satisfaction--Reference librarians--Philippines.